University Learners’ Perspective towards Factors Affecting the Speaking Skill - Jezhny, Karzan A.; Bapir, Nazenin S.M (Mağallaẗ ğāmiʻaẗ Ğīhān- Arbīl li-l-ʻulūm al-insāniyyaẗ wa-al-iğtimāʻiyyaẗ, 2021)
This study is an attempt to explore the essential factors that affect the Speaking Skill of English language learners (ELLs). Its primary objective is to give an analysis of the perspective of the participants in respect of the central factors influencing the speaking skill. The knowledge of the participants concerning the issues pertinent to the speaking skill is presented. The study adopts a mixed-methods research approach: a combination of quantitative and qualitative methods. A structured questionnaire and interviews are instruments of data collection which are analyzed statistically and descriptively. The study lays emphasis on the significance of the speaking skill. After presenting the literature review, it sheds light on factors that affect the speaking skill. Following this, features of the speaking skill are highlighted. The findings of the study signals that there are methodological, linguistic-related and psychological factors influencing the speaking skill of ELLs. And the most influential factors are oral practice, range of vocabulary and self-confidence.